Hubungan Status Pekerjaan terhadap Tingkat Partisipasi Sosial di Komunitas Pesisir Malabero - Ahmad Zulpikri; Lara Dwi Tamara; Bunga Susiana; Doti Permata Sari; Agelia Dwi Pasela; Heni Nopianti; Ika Pasca Himawati (CV. Lentera Literasi Indonesia, 2026)
Coastal communities are a social group whose livelihoods are highly dependent on marine resource-based economic activities. This situation creates a predominantly informal employment structure characterized by long working hours and uncertain incomes. This situation has the potential to impact the community's level of social participation in community life. This study aims to analyze the relationship between employment status and the level of social participation in the Malabero coastal community, Bengkulu City. This study used a quantitative approach with a survey method. A total of 175 respondents were selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using the Kendall's Tau correlation test. The results indicate that the level of social participation in the Malabero coastal community is in the low (weak) correlation category. The correlation test results show a Kendall's Tau coefficient of τ = –0.241 with a significance value of p = 0.000, indicating a significant relationship between employment status and level of social participation. The negative direction of the relationship indicates that the higher the demands of employment status, the lower the level of social participation. These findings suggest that employment status is a significant factor influencing the social involvement of coastal communities. Therefore, social policies and programs are needed that are adaptive to the working conditions of coastal communities in order to increase social participation without ignoring the economic needs of the community.